Impact of an Advanced Cardiac Life Support Simulation Laboratory Experience on Pharmacy Student Confidence and Knowledge - Maxwell, Whitney D. (Am J Pharm Educ, 2016)
Objective. To assess the impact of an advanced cardiac life support (ACLS) simulation on pharmacy student confidence and knowledge. Design. Third-year pharmacy students participated in a simulation experience that consisted of team roles training, high-fidelity ACLS simulations, and debriefing. Students completed a pre/postsimulation confidence and knowledge assessment. Assessment. Overall, student knowledge assessment scores and student confidence scores improved significantly. Student confidence and knowledge changes from baseline were not significantly correlated. Conversely, a significant, weak positive correlation between presimulation studying and both presimulation confidence and presimulation knowledge was discovered. Conclusions. Overall, student confidence and knowledge assessment scores in ACLS significantly improved from baseline; however, student confidence and knowledge were not significantly correlated.